Chlamydia Pneumoniae Infection and Cerebral Infarction Risk: A Meta-Analysis. Issue 3 (April 2014) - Su, Xing; Chen, Hong-Lin
Background Chlamydia pneumoniae: infection and the risk of cerebral infarction have been previously studied in several publications; however, conflicting results have been reported. This meta-analysis assessed whether C. pneumoniae infection was associated with risk of cerebral infarction. Methods: Systematic computerized searches of the PubMed and Web of Knowledge were performed. Adjusted odds ratio and 95% confidence interval from original studies were extracted for combined meta-analysis. Results: Twenty-three studies with 2924 cerebral infarction patients and 4692 control patients were included in the meta-analysis. When the positive C. pneumoniae infection was defined by microimmunofluorescence-detected immunoglobulin A, the pooled odds ratio between two groups was 2·04 (95% confidence interval 1·42–2·9). In the most frequently used immunoglobulin A ⩾1:16 sub-group, the pooled odds ratio was 2·07 (95% confidence interval 1·31–3·26). When the infection was defined by enzyme-linked immunosorbent assay-detected immunoglobulin A, the pooled odds ratio was 2·89 (95% confidence interval 1·23–6·81). When the infection was defined by microimmunofluorescence-detected immunoglobulin G, the pooled odds ratio was 1·46 (95% confidence interval 1·18–1·81). In the most frequently used immunoglobulin G ⩾1:32 sub-group, the pooled odds ratio was 1·43 (95% confidence interval 1·06–1·92). When the infection was defined by enzyme-linked immunosorbent assay-detected immunoglobulin G, the pooled odds ratio was 1·54 (95% confidence interval 0·86–2·74). No significant publication bias was found. Sensitivity analyses showed the results were robust. Conclusion (1 ) This meta-analysis indicated that C. pneumoniae infection was significantly associated with an increased risk of cerebral infarction. (2 ) Compared with anti- C. pneumoniae immunoglobulin G, anti- C. pneumoniae immunoglobulin A seemed more effective for predicting the risk of cerebral infarction. (3 ) No evidence existed that anti- C. pneumoniae -immunoglobulin G detected by enzyme-linked immunosorbent assay could predict the risk of cerebral infarction.